Consequences of Implementing Curricular-Aligned Strategies for Identifying Rural Gifted Students. (October 2022) - Callahan, Carolyn M.; Azano, Amy; Park, Sunhee; Brodersen, Annalissa V.; Caughey, Melanie; Dmitrieva, Svetlana
Analysis of assessment data from an initial pool of second-grade students ( n = 4549) in low-income rural communities and a subgroup of students identified from that pool for gifted services ( n = 524) provided evidence for the validity of a curricular-aligned process including universal screening and local norms for identifying rural students in high-poverty schools as gifted. We first compared identification data on a group identified with existing, more general identification strategies to data on students identified specifically in language arts using universal screening and local norms as part of the identification criteria, providing staff development focused on indicators of rural giftedness prior to teacher ratings of students, and using a profile in decision making. This comparison confirmed the hypothesis that talent in rural students from low-income areas may manifest in ways that are not captured by more generic identification processes. Despite concerns about the implementation of identification processes using local norms, students identified through the project's alternative approach scored higher on a measure of verbal aptitude and scored as well on postintervention assessments as students identified using the district-identification process. This outcome provides evidence that students identified with local norms in a specific academic domain reach similar or higher levels of achievement as students identified using national norms and more general means of assessment.